Prevalence of obesity and its associated psychological factors and mindful eating among medical students: a cross sectional study in UPM - Thew, Hui Zhu; Mohamad, Fadzilah; Mohd Shahrim, Afifah Husna; Abdul Rahim, Muhammad Hafiy Akmal; Aravandy, Puravin Raj; Chew, Chen Loong Alyx; Yap, Qiao Rou Amelia; Fong, Yan Bin (Universiti Putra Malaysia, 2023)
Introduction: There is a tremendous prevalence of obesity worldwide, among both adults and children. Obesity may be caused by various factors, including genetic factors, psychosocial stresses, and environmental factors. Some local studies showed that the prevalence of obesity is high among undergraduate medical students, which might impact the quality of life of the medical students. The objective of this study is to determine the prevalence of obesity among UPM medical students and its associated factors, including sociodemographic factors, levels of mindful eating, and psychological factors. Method: A cross sectional study was performed on 483 medical students between 20 and 26 years old who were selected via universal sampling method. Through a google form, medical students were sent a self-administered online questionnaire that included sections on sociodemography, psychological distress, MEQ scores, and self-reported weight and height. Results: The majority of the respondents were female undergraduate medical students (66.9%). Out of 483 respondents, 166 were obese (34.4%). Multivariate logistic regression analysis shows that gender (p <0.001, β: 1.018), age (p:0.014, β:0.156), ethnicity (Chinese: p<0.001, β-1.020) and total MEQ scores (p <0.001, β:1.669) were statisticly significant associated with obesity. Conclusion: In summary, this study explores obesity prevalence and its associated factors among UPM medical students, including sociodemographics, mindful eating, and psychological aspects. The factors of this study which were significant associated with obesity were gender, age, ethnicity and total MEQ scores. By recognizing the myriad variables intertwined with obesity development, we can now design more targeted interventions for obesity prevention. This broader perspective compels a shift from one-size-fits-all approaches to tailored solutions that address the unique needs and susceptibilities of individuals.